Empire and information : intelligence gathering and social communication in India, 1780-1870 - Bayly, C. A. (Christopher Alan) (Cambridge ; New York : Cambridge University Press, 1999)
Deploying a superior military strength and a sophisticated intelligence system allowed the British to conquer India. In a penetrating account Bayly shows how networks of Indian spies were recruited by the British to secure information
Prologue: surveillance and communication in early modern India -- Political intelligence and indigenous infomants during the conquest of India, c. 1785-185 -- Misinformation and failure on the fringes of empire -- Between human intelligence and colonial knowledge -- The Indian ecumene: an indigenous public sphere -- Useful knowledge and godly society, c. 1830-50 -- Colonial controversies: astronomers and physicians -- Colonial controversies: language and land -- The information order, the rebellion of 1857-9 and pacification -- Epilogue: information, surveillance and the public arena after the rebellion -- Conclusion: 'knowing the country'
Originally published: 1996
Includes bibliographical references (pages 377-400) and index
Keywords: Intelligence service -- India -- History; Communication -- Social aspects -- India -- History; India -- Politics and government -- 1765-1947